Prosopagnosia as a Type of Conversion Disorder. (13th February 2018) - Power, Clodagh; Hannigan, Oisin; Coen, Robert; Bruce, Irene; Gibb, Matthew; McCarthy, Marie; Robinson, David; Lawlor, Brian A.
Abstract : Background . Conversion disorder is a common and debilitating condition that remains poorly understood. We present a previously undescribed form of conversion disorder to highlight the complexity of the condition and consider the interplay of factors that produce conversion symptoms. Case . A 50-year-old male presented with acquired prosopagnosia and language impairment. Neuropsychological testing indicated right temporal lobe dysfunction. Extensive work-up outruled an organic aetiology. Reactivation of childhood trauma coincided with the onset of his symptoms. Childhood trauma is known to have adverse effects on the developing brain which may affect an individual's emotional behaviour and coping style. Functional neuroimaging techniques suggest that conversion symptoms may be linked to the disruption of higher order neural circuitry involved in the integration of emotional processing and cortical functioning. Conclusions . We propose that our patient's adverse childhood experiences led to the development of a particular personality and coping style that "primed" him for a later abnormal emotional and behavioural response when confronted with reminders of his traumatic background. Further interdisciplinary studies are required to further elucidate the neurobiological basis for this condition.